Superstring theory on AdS(2) x S-2 as a coset supermanifold - Berkovits, N.; Bershadsky, M.; Hauer, T.; Zhukov, S.; Zwiebach, B. (Elsevier B.V., 2000)
We quantize the superstring on the AdS(2) X S-2 background with Ramond-Ramond flux using a PSU(1,1\2)/U(I) X U(1) sigma model with a WZ term. One-loop conformal invariance of the model is guaranteed by a general mechanism which holds for coset spaces G/H where G is Ricci-flat and H is the invariant locus of a Z(4) automorphism of G. This mechanism gives conformal theories for the PSU(1,1\2) X PSU(2\2)/SU(2) X SU(2) and PSU(2,2\4)/SO(4,1) X SO(5) coset spaces, suggesting our results might be useful for quantizing the superstring on AdS(3) X S-3 and AdS(5) X S-5 backgrounds. (C) 2000 Elsevier B.V. B.V. All rights reserved.